2003
DOI: 10.1159/000072880
|View full text |Cite
|
Sign up to set email alerts
|

Association of Muscarinic M1 Receptor Genetic Polymorphisms with Psychiatric Symptoms and Cognitive Function in Schizophrenic Patients

Abstract: Objective: The cholinergic system is important in the search for the pathophysiology of schizophrenia due to its role in cognitive function, interaction with the dopamine system in brain regions relevant to schizophrenia, side effects of antipsychotic medication and potential antipsychotic effect of muscarinic receptor antagonists. This study investigated the association of type I muscarinic receptor (CHRM1) genetic polymorphisms with the clinical characteristics of chronic schizophrenic inpatients. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Importantly, while we detected only 5 of the 11 CHRM1 SNPs previously reported, 30 the SNPs we failed to detect occur mainly in African Americans and Hispanic populations, 30 which are not represented in our cohorts. Moreover, we have confirmed a previous finding 16 of complete linkage between the c.267C > A and c.1353C > T SNPs. Although our data identify possible changes in SNP frequencies in schizophrenia, there is the potential for a type I error in our study due to the relatively small sample size.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, while we detected only 5 of the 11 CHRM1 SNPs previously reported, 30 the SNPs we failed to detect occur mainly in African Americans and Hispanic populations, 30 which are not represented in our cohorts. Moreover, we have confirmed a previous finding 16 of complete linkage between the c.267C > A and c.1353C > T SNPs. Although our data identify possible changes in SNP frequencies in schizophrenia, there is the potential for a type I error in our study due to the relatively small sample size.…”
Section: Discussionsupporting
confidence: 91%
“…12 Furthermore, the availability of more selective tools has made it possible to show that it is the cortical CHRM1 that is selectively decreased in schizophrenia. [13][14][15] Moreover, a recent finding that the c.267C/C genotype at the c.267A/C polymorphism in the CHRM1 is associated with more severe cognitive deficits in schizophrenia, 16 suggests that variation in CHRM1 gene sequence and/or expression might be associated with a key symptom of the disorder. Together, these data suggest that abnormalities in CHRMs may significantly contribute to the pathology of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…199 A polymorphism of the M 1 muscarinic receptor gene was associated with a better score on the Wisconsin Card Sorting Test in schizophrenia. 200 No other genetic studies have been reported on the muscarinic cholinergic system in schizophrenia so far.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from Japanese subjects was genotyped for ϩ267A Ͼ C (rs2067477) and ϩ1353C Ͼ T (rs2067480), because an association of these polymorphisms at the muscarinic M1 receptor gene with cognitive function in schizophrenic patients has been reported (19). We selected an additional seven SNPs for genotyping based on the frequency and location of SNPs and the linkage disequilibrium (LD) structure in and around the CHRM1 gene.…”
Section: Identification Of Polymorphismsmentioning
confidence: 99%